Identifying Determinants of Firefighter Work Health and Task Performance: Implications for Injury Management - Sinden, Kathryn E. (My University, 2014)
Introduction: Applied occupational health research is complex and requires transparent communication between stakeholders to facilitate development and implementation of injury management strategies. Firefighting as a physically demanding, male-dominant occupation provides a unique context to develop and implement injury management strategies. Thesis Objectives: To investigate how individuals perform occupational tasks within a physically demanding occupational context considering the interrelationship between personal, task and environmental factors. A secondary objective was to evaluate the research partnership as integrated knowledge translation using the Knowledge-to-Action (KTA) Framework. Methods. A qualitative study was used to identify barriers and facilitators experienced by female firefighters. Dartfish movement analysis software was adapted to analyze kinematics associated with firefighter tasks. Relative and absolute reliability was used to establish measurement properties of Dartfish methods. Regression models identified the relative importance of individual factors on firefighter task performance. A case study of the research partnership using knowledge translation (KT) theory identified critical phases in developing occupational health research partnerships. Results. The qualitative study identified sex/gender and task/environment effects on firefighter task performance and injury risk. Tracking positional co-ordinate data using Dartfish demonstrated excellent relative reliability (ICC2,1 = 0.84-0.99) and lowest absolute reliability (SEM = 0.01m-0.11m). Strength was the strongest independent predictor of firefighter task performance time where increasing strength was associated with faster time. The case study identified components of the KTA Action Cycle that supported and described collaborative occupational health research. Conclusions. Although female firefighters share commonalities with their male counterparts, unique personal attributes and social experiences affect how they experience firefighting. Dartfish provides a reliable tool to measure kinematics in an applied context. Although refinements are required, recommendations for data collection and extraction using Dartfish in occupational contexts are provided. Occupational health research imbedded in KTA cycle confirms the importance of partnership with stakeholders to ensure the feasibility and relevance of the research.
Keywords: Occupational Health, Firefighters, Ergonomics, Integrated Knowledge Translation